Commodity tax competition - purchases of spirits in the Scandinavian countries - Odd Erik Nygård (Statistics Norway, Research Department, 2009)
A simulation model consisting of a representative consumer for each Scandinavian country is constructed and calibrated, in which consumers consume two goods: spirits and 'other goods'. Spirits is exposed to cross-border shopping, and the countries engage in tax competition. The equilibrium tax rates show large price differentials on spirits in Scandinavia. The findings also suggest that Norway and Denmark pay more attention to cross-border shopping and tax competition when setting the tax rates compared to Sweden. Furthermore, the equilibrium tax rates are rather robust with respect to the type of game that we consider, due to the fact that the utility maximizing tax rate for each country is rather insensitive with respect to other countries' tax rates. Nevertheless, the sequential game equilibrium consists of somewhat higher taxes and utility levels for each country compared to the simultaneous game equilibrium, meaning that the former equilibrium Pareto-dominates the latter.
Keywords: C7; D12; H1; H31; 330; indirect taxes; excise taxes; cross-border shopping; commodity tax competition; alcohol; spirits; optimal taxation